Autistic Adult Services Availability, Preferences, and User Experiences: Results From the Autism Spectrum Disorder in the European Union Survey - Micai, Martina; Fulceri, Francesca; Salvitti, Tommaso; Romano, Giovanna; Poustka, Luise; Diehm, Robert; Iskrov, Georgi; Stefanov, Rumen; Guillon, Quentin; Rogé, Bernadette; Staines, Anthony; Sweeney, Mary Rose; et al. (Frontiers in Psychiatry, 2022)
There is very little knowledge regarding autistic adult services, practices, and delivery. The study objective was to improve understanding of current services and practices for autistic adults and opportunities for improvement as part of the Autism Spectrum Disorder in the European Union (ASDEU) project. Separate survey versions were created for autistic adults, carers of autistic adults, and professionals in adult services. 2,009 persons responded to the survey and 1,085 (54%) of them completed at least one of the services sections: 469 autistic adults (65% female; 55% < 35 years old), 441 carers of autistic adults (27% female; 6% < 35 years old), 175 professionals in adult services (76% female; 67% in non-medical services). Top choices by autistic adults, carers or professionals for services best suiting their current needs were: residential services: ‘help in own home’ (adults, carers of high independent adults, professionals), ‘fulltime residential facility’ (carers of low independent adults); employment services: ‘job mentors’ (adults, carers of high independent adults, professionals), ‘Sheltered employment’ (carers of low independent adults); education services: ‘support in regular education setting’ (all groups); financial services: financial support in lieu of employment (‘Supplementary income for persons unable to have full employment’ for adults, ‘full pension’ for carers of low independent adults) or to supplement employment earnings for carers of high independent adults and professionals; social services: ‘behavior training’ (adults) and ‘life skills training’ (carers and professionals). Waiting times for specific services were generally <1 month or 1-3 months, except for residential services which could be up to 6 months; most professionals were uninformed of waiting times (> 50% responded ‘don’t know’). Five of seven residential services features recommended for autistic adults were experienced by <50% of adults. The knowledge of good local services models that work well for autistic adults was generally low across all services areas. The variation in services experiences and perceptions reported by autistic adults, carers, or professionals underscore the need to query all groups for a complete picture of community services availability and needs. The results showed areas for potential improvement in autistic adult services delivery in the EU to achieve recommended standards.